Improving employee performance on work efficiency: a survey in employee productivity in Malaysia during COVID-19 pandemic age / Lee Yu Nan ... [et al.] - Lee, Yu Nan; Haw, Yen Nee; Ho, Hong Ren; Mohd Johan, Mohd Remie (Universiti Teknologi MARA, Perlis, 2023)
The COVID-19 pandemic has caused a significant impact on the workplace, particularly on employee productivity. Due to the worldwide COVID-19 pandemic, businesses and employees have been restricted from travelling to prevent the spread of the virus. Working from home is growing increasingly prevalent in the current digital age and employees are urged to be accommodated. This study aims to investigate employee productivity in Malaysia during COVID-19. Our research objective for this research is to evaluate employee satisfaction, compensation and benefits, training and development and organizational culture factor contribution to the employee performance on work efficiency in Malaysia during COVID-19 Pandemic Age. Our conceptual framework includes four independent variables, namely employee satisfaction, compensation and benefits, training and development and organizational culture and they have an impact on employee performance. Moreover, this study mainly uses quantitative research method, and it adopts a survey methodology to collect data from employees in various organizations in Malaysia. Descriptive and inferential statistical analyses are used to analyze the data.